"For me, it's a real pain": A Foray into the Experience of Parents Involved in Family-Based Treatment. (January 2023) - Thibault, Isabelle; Leduc, Karissa; Tougas, Anne-Marie; Pesant, Caroline
Eating disorders are undoubtedly challenging for the adolescents experiencing them, but they can also be challenging for their parents. The current study employed a qualitative research design to examine the challenges endured by parents raising adolescents with eating disorders and undergoing a Family-Based Treatment (FBT) program. Six mothers of adolescents with anorexia nervosa or bulimia were interviewed about the challenges they face as parents of a child with an eating disorder and the changes they have had to make in their lives. Overall, results highlighted challenges from a personal, family, and parental role lens. Findings also call attention to the difficult responsibilities placed on parents during FBT programs such as involvement in their child's refeeding plan and the emotional toll their child's experience places on them. Implications for the level of support needed by parents are discussed according to their role in FBT programs.